(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
In the early nineteenth-century annuals, Dante plays a particularly important role. The paper addresses two profoundly different texts, namely the Ettore e Andromaca, Paolo e Francesca, Giulietta e Romeo by Luigi Carrer and a sonnet by Benedetto Vollo dedicated to the reading experience of Canto V. The two texts are united as well by the professional relationship that binds the two authors. The educational text of Carrer and the sonnet of the Vollo are examined in relationship to the cultural profile of the annuals and the reception of the readers, as well as to the contemporary Dante critics.